Torture on Goli Otok Through the Prism of Psychology in the Works of Petar Kostić - Miroslav,; Jaredić, Biljana (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The subject of this research is the scientific contribution of the psychologist Petar Kostić, as an objective scientist, in the analysis and interpretation of the methodology of torture in the camp for political prisoners on Goli otok, through the prism of psychology. The central part illuminates the theoretical determinationsand the scientific model of the system of “self-directed” re-education in the Goli Otok, through the action of psychological behaviors as an experimental frame of the Skiner’s type and brainwashing as a practical system of “self-directed” re-education. The paper discusses further topics related to the abuse of psychology in shaping human behavior, the composition and functioning of the system of “self-directed” upbringing, the psychological supportive personality system that implicitly starts from the psycho-ecological theory of human beings: body, belonging, thinking and purpose, faith and hope , Milgram’s, Ashе’s and Zimbardо's experiments in “self-directed” re-education. At the end of the paper, the implications for mental health are explained and what, in some Naked island victims, helped them to survive and be functional after the torture they have survived.
Keywords: Torture; Goli otok Island; “Goli otok’s experiment of self-directed re-education”; “brainwashing”; abuse of psychology in shaping human behavior